Evaluation of the Antimicrobial Activity of the Leaf and Seed Extracts of Moringa oleifera on Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa - A, Mbata Christian; Adebayo, Adegoke O.; Chinyere, Nwagu; Cecilia, Dimkpa (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
The aim of the study was to ascertain the antimicrobial activities of the extract of Moringa oliferea leaf and seed, to compare the size of the inhibition zone on bacteria isolates, and to ascertain the different concentration of Moringa oleifera seed and leaf that shows inhibition. For thousands of years, ancient people depended mostly on flowers, barks, leaves and fruits of plants for medicine. Only recently have synthetic drugs, most of which are similar to compounds identified in plants, come into use. Information on the activities and curative actions of medicinal plants was obtained from the introduction of the European scientific method. Specifically, this study focused on the antimicrobial activity of alcohol (ethanol) and aqueous extracts of Moringa oleifera seed and leaf on Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. The plant material of Moringa oleifera leaves and seeds used in this study was collected from Dilomat Farms and Service Limited in Rivers State University of Science and Technology, Nkpolu–Oroworuwku, Port Harcourt, Rivers State. The ethanol and aqueous extracts of the seed and leaf at a concentration of 10g/100ml and the diluted ethanol and aqueous extracts at concentrations of 0.1g/ml, 0.2g/ml, 0.4g/ml, 0.6g/ml and 0.8g/ml were impregnated into sterilized filter paper discs. Also, ethanol alone was impregnated into sterilized filter paper discs and used as a control. The agar disc diffusion method was adopted to obtain zones of inhibition. The zones of inhibition obtained for ethanol extract of Moringa oleifera seed for Staphylococcus aureus was 12 mm, Escherichia coli was 13 mm and Pseudomonas aerucginora was 10 mm. The ethanol extract of Moringa oleifera leaf gave an inhibitory zone of 11 mm for Staphylococcus aureus, 10mm for Escherichia coli, and 9mm for Pseudomonas aeruginosa. Different degrees of inhibition were observed for the diluted ethanol extracts of Moringa oleifera seed. The diluted ethanol extracts of Moringa oleifera leaf were resistant to the test organisms at concentrations of 0.1g/ml, and 0.6g/ml but were sensitive at concentrations of 0.8g/ml. The aqueous and diluted aqueous extracts of Moringa oleifera seed and leaf were resistant to the test organisms. The zones of inhibition obtained for ethanol alone on the test organisms ranged between 8mm and 10mm. The degree of the zone of inhibition differs, however, the ethanol extracts exhibited the highest inhibitory effect than the aqueous extracts. This study revealed that Moringa oleifera seed and leaf extracts are potential antimicrobial agents. It should be used successfully for treating food poisoning, wound, diarrhea, dysentery, boil, sexually transmitted diseases and arthritis caused by the test organisms. The addition of Moringa oleifera to meals is highly recommended. Additionally, there is a need for detailed scientific study of traditional medical practices to ensure that valuable therapeutic knowledge of some plants is preserved and to provide scientific evidence for their efficacies.